A Review Study of Analysis of Tool Chatter in Turning Operation and Control Methods: Approaches to minimize tool chatter in turning operations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Machine tool chatter is one of the most significant bottlenecks in the turning operation. It's a self-excited vibration induced by the association of the machine toolworkpiece arrangement with the cutting mechanism dynamics. The nonlinearity of dry friction and the irregular interaction between the cutting instrument and the workpiece are the primary causes of frictional and effect chatter. There are a few ways to keep the chatter to a minimum. We will implement and compare some of these approaches in this article.